Untreated sleep apnea and left atrial dilatation in patients with atrial fibrillation prior to catheter ablation. (3rd October 2022) - Tanaka, N; Okada, M; Tanaka, K; Harada, S; Kawahira, M; Hirao, Y; Onishi, T; Koyama, Y; Fujii, K; Watanabe, H; Okamura, A; Iwakura, K
Abstract: Background: Sleep apnea and left atrial dilatation are both risk factors for an arrhythmia recurrence after catheter ablation (CA) of atrial fibrillation (AF). Negative intrathoracic pressure fluctuations during an obstructive apnea episode may cause the left atrium to distend and stretch its wall. Whether sleep apnea is associated with left atrial dilatation in patients receiving CA of AF remains unknown. Purpose: We sought to elucidate whether moderate or severe untreated sleep apnea was associated with left atrial dilatation in patients with AF before CA. Methods: This study was conducted under a retrospective, single-center, observational design. The data were derived from screening tests for sleep apnea, which were routinely performed in patients scheduled to receive CA of AF in our institution. After excluding patients who were already diagnosed with sleep apnea, we enrolled 1265 consecutive patients (age 65±11 years, 27.8% females, and 46.2% of non-paroxysmal AF) who underwent both home sleep apnea testing and multidetector computed tomography (MDCT) before the CA of AF. The severity of the sleep apnea was evaluated by the apnea-hypopnea index (AHI) using a watch-type peripheral arterial tonometry. Left atrial dilatation was evaluated by the left atrial maximum volume (LA max V) using 256-slice MDCT. Results: The age was 65±11 years, 27.8% were females, and 46.2% had non-paroxysmal AF. The mean AHI was 20.3±15.3 and LA max V 105±34 ml (R2=0.075, p<0.0001). LA dilatation was defined by larger than mean LA max V (LA max V≥105 ml). We examined an LA max V≥105 ml as a predictor. After an adjustment by an advanced age (≥65 years), non-paroxysmal AF, male sex, obesity, hypertension, and congestive heart failure, all of which were significant predictors of an LA max V≥105ml in the univariate analysis, moderate or severe sleep apnea (AHI≥15) was a significant predictor of an LA max V≥105 ml (odds ratio 1.63, 95% confidence interval 1.24–2.14, p=0.0005). Conclusion: Among the patients scheduled to receive catheter ablation of AF, moderate or severe sleep apnea was independently associated with left atrial dilatation. Funding Acknowledgement: Type of funding sources: None.